Sosialisasi dan Penyuluhan Kesehatan Bahaya Narkotika dan Sanksi Hukum di Kelurahan Manisa Kabupaten Sidenreng Rappang - Bachri, Syaiful; Nurhaedah, Nurhaedah; Cahyanta, Agung Nur; Verawati, Verawati; Pannyiwi, Rahmat; Purwoto, Ady (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Sidenreng Rappang Regency, South Sulawesi Province is known as the Rice Granary area, recently this positive stigma has shifted that Sidenreng Rappang Regency is now better known as the Drug Granary which is one of the centers of drug trafficking in South Sulawesi. Manisa Village is one of the Villages located in the Baranti District which has a fairly large community. Manisa Village is very active in collaborating with agencies in Sidenreng Rappang Regency in holding counseling and socialization related to the dangers of narcotics. The purpose of this activity is to increase supervision and control as an effort to prevent and eradicate drug abuse and trafficking in the community. The method in the activity is Socialization and Health Counseling on the Dangers of Narcotics and Legal Sanctions in Manisa Village, Sidenreng Rappang Regency by delivering material related to the material on the legal basis of the Narcotics and Psychotropic Law and its legal impacts. The results showed that the participants were very enthusiastic in discussing with the resource persons in increasing the participants' insight and knowledge to find out how to prevent and reject drugs in the community. The conclusion that in overcoming the problem of drug abuse faced by the community in finding solutions and the lack of public knowledge about how to prevent and overcome drug abuse and its negative impacts on children and the community itself. By providing continuous counseling or socialization so that the community understands how to behave towards the spread of narcotics.